Understanding the Work/Life Balance of Student-Mothers in Online Graduate Programs - Michelle Covert (Adult Education Research Conference, 2014)
This qualitative study presents an overview of the work/life balance of four student-mothers in online graduate programs focusing on issues such as feelings of tiredness, guilt, and being overwhelmed, support from spouses, division of household labor, homework interruptions, and children’s well-being.